Pembuatan Website Adopsi Hewan Khusus Kucing dan Anjing Menggunakan Laravel - Yovan Fajar Nurizal; Isram Rasal (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this website development is to assist and provide effectiveness in increasing public awareness regarding animal care practices, as well as to facilitate shelters in presenting information on stray animal adoption. Additionally, this website also facilitates donations that will be used to provide health services to stray animals. This platform also functions as a promotional medium for animal-related events, such as adoption events, education, and socialization of proper animal care. Through these features, it is expected that a better relationship can be created between the community and shelters, and that more stray animals can obtain decent housing and necessary care. Website testing was conducted using the black box testing method, where all functionalities were tested without looking at the internal code. Based on the test results, all systems were declared to function properly according to the expected specifications. The development method for this website uses the SDLC (System Development Life Cycle), which consists of several main stages, namely: the planning stage where the system's objectives and needs are identified, the analysis stage that focuses on user needs, the design stage where the interface and system structure are developed, and the implementation and testing stage, which involves website creation, testing, and improvements based on the test results. By following the SDLC method, the website is expected to run optimally and meet user needs.